An Erwinia amylovora uracil transporter mutant retains virulence on immature apple and pear fruit. (October 2020) - Bittner, Amanda J.; Huntley, Regan B.; Mourad, George S.; Schultes, Neil P.
Abstract: Erwinia amylovora is the causal agent of fire blight, a devastating disease of apples and pears. A previous study revealed that an E. amylovora uracil auxotroph was still virulent and can cause disease, suggesting that uracil can be obtained from the host environment. The E. amylovora genome contains a locus encoding for a uracil transporter belonging to the nucleobase cation symporter 2 family, displaying a high level of amino acid sequence similarity to the Escherichia coli UraA. Expression of E. amylovora UraA in nucleobase transporter-deficient E. coli strains, coupled with radiolabeled uptake studies reveal that E. amylovora UraA is a high affinity uracil transporter with a Km of 0.57 μM. Both E. coli and E. amylovora carrying extra copies of E. amylovora UraA are sensitive to growth on the toxic analog 5-fluorouracil. An E. amylovora ΔuraA::Cam r mutant is still able to grow and cause disease symptoms on immature pears and apples. Highlights: E. amylovora causes fire blight. EaUraA transports uracil. An E. amylovora uraA mutant is virulent.